Factors associated with dental visit and barriers to the utilization of dental services among tribal pregnant women in Khurda district, Bhubaneswar: A cross-sectional study - Diplina Barman; Rajeev Ranjan; Anirban Kundu (Wolters Kluwer Medknow Publications, 2019)
Background: There is a lack of knowledge related to the utilization of dental services by tribal pregnant women who constitute over 35% of the Indian population. The aim of the present study was to identify barriers to the utilization of the dental services and also the factors that concern the tribal mothers' visit to the dental office. Materials and Methods: A total of 300 tribal mothers visiting a tertiary care unit participated in this cross-sectional, observational study. A pilot study with twenty participants was conducted before the commencement of the study. Data were collected using a modified questionnaire consisting of demographic data and questions relating to oral health knowledge, attitude, and practices, as well as barriers to the utilization of dental services and factors that concern dental visits during pregnancy. Data analysis was done using SPSS software package 21.0. Nonparametric statistical tests were done to analyze oral health knowledge and attitude of the participants. Various factors were identified using univariate and multivariate models using simple logistic regression analysis and multiple logistic regression analysis. Results: Among the two different tribes considered in the present study, the Saora tribe seemed to be more conscious toward oral health, and 29.7% of participants visited the dentist during pregnancy. The age and experience of the participants along with the educational level, employment status, and knowledge about oral health-related pregnancy outcomes influenced their dental visits. The most reported barrier included the lack of awareness and knowledge of the availability of the dental services. Accessibility and distance to the dental clinic were not found to be negative confounding factors among the participants for the utilization of the services. Conclusion: This study concludes that previous experience and consciousness of the mother to utilize the dental services played a vital role in the utilization of dental services among tribal pregnant women. However, the findings of the present study clearly indicate the need for further research to understand barriers to the utilization of dental services among underprivileged tribal groups of population.